The CBL and CIPK Gene Family in Grapevine (Vitis vinifera): Genome-Wide Analysis and Expression Profiles in Response to Various Abiotic Stresses - Xi, Yue; Liu, Jinyi; Dong, Chao; Cheng, Zong-Ming (Max) (Frontiers in Plant Science, 2017)
Calcium plays a central role in regulating signal transduction pathways. Calcineurin B-like proteins (CBLs), which harbor a crucial region consisting of EF hands that capture Ca2+, interact in a specific manner with CBL-interacting protein kinases (CIPKs). This two gene families or their interacting-complex widely respond to various environment stimuli and development processes. The genome-wide annotation and specific expression patterns of CBLs and CIPKs, however, in grapevine remain unclear. In the present study, eight CBL and 20 CIPK genes were identified in grapevine genome, and divided into four and five subfamilies, respectively, based on phylogenetic analysis, and validated by gene structure and the distribution of conserved protein motifs. Four (50%) out of eight VvCBLs and eight (40%) out of 20 VvCIPKs were found to be derived from tandem duplication, and five (25%) out of 20 VvCIPKs were derived from segmental duplication, indicating that the expansion of grapevine CBL and CIPK gene families were mainly contributed by gene duplication, and all duplication events between VvCIPK genes only detected in intron poor clade. Estimating of synonymous and non-synonymous substitution rates of both gene families suggested that VvCBL genes seems more conserved than VvCIPK genes, and were derived by positive selection pressure, whereas VvCIPK genes were mainly derived by purifying selection pressure. Expressional analyses of VvCBL and VvCIPK genes based on microarray and qRT-PCR data performed diverse expression patterns of VvCBLs and VvCIPKs in response to both various abiotic stimuli and at different development stages. Furthermore, the co-expression analysis of grapevine CBLs and CIPKs suggested that CBL-CIPK complex seems to be more responsive to abiotic stimuli than during different development stages. VvCBLs may play an important and special role in regulating low temperature stress. The protein interaction analysis suggested divergent mechanisms might exist between Arabidopsis and grapevine. Our results will facilitate the future functional characterization of individual VvCBLs and VvCIPKs.